Physico-chemical and sensory characterizations of three types of « dèguè », a local fermented drink made from milk in Benin - TCHEKESSI, C. K. Célestin; BOKOSSA, Auréole; ADIGUN, Nadège; BLEOUSSI, Roseline Myriam; SACHI, Pivot S. A.; BOKOSSA YAOU, Innocent Padonou; BANON, Jultesse; AGBANGLA, CLÉMENT (My University, 2014)
Dèguè is a fermented drink widely consumed in Benin and other countries of West Africa. Our study permitted to finalize three types of dèguè made from flours of maize, sorghum and millet, called respectively: dèguè maize, dèguè sorghum and dèguè millet. To increase consumer confidence and ensure their products good qualities, these three types of dèguè were evaluated and analyzed the physico-chemical and sensory plans. The results of analysis revealed that the three types of dèguè obtained contain iron, protein and sugar. All have an acidic taste with a pH below 4.3. Dèguè millet is richer in iron (38.32mg/100g) than the other two dèguès. Dèguè sorghum contains up to 21.59mg/100g, while dèguè maize contains only 18.21mg/100g. Dèguè maize is lightly richer in protein (13.95%) than dèguè mil (13.93%) and dèguè sorghum (13.64%). However, dèguè millet is sweeter (9.50%) than dèguè maize (6.47%) and dèguè sorghum (5.29%). Furthermore, all types of dèguè contain vitamins B1, B2 and C, however dèguè sorghum contains two more, it is of vitamins E and A of which the contents reach 6.76mg/100g and 8.69mg/100g respectively. Sensory analysis revealed that all three types of dèguè finalized accepted by the tasters. In view of these results, the consumption of dèguè sorghum is recommended.
Keywords: Cereals; fermented milk; dèguè; nutritional value.